2021
DOI: 10.1155/2021/4117800
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Effects of Pulmonary Surfactant Combined with Noninvasive Positive Pressure Ventilation on KRT‐14 and ET‐1 Levels in Peripheral Blood and Therapeutic Effects in Neonates with Respiratory Distress Syndrome

Abstract: This study is aimed at exploring the effect of pulmonary surfactant (PS) combined with noninvasive positive pressure ventilation on the levels of Keratin-14 (KRT-14) and Endothelin-1 (ET-1) in peripheral blood and the therapeutic effect of neonatal respiratory distress syndrome (NRDS). Altogether 137 cases of neonates with respiratory distress syndrome treated in our hospital from April 2016 to July 2018 were collected. Among them, 64 cases treated with noninvasive positive pressure ventilation were considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%